2011
DOI: 10.1386/ctl.7.1.35_1
|View full text |Cite
|
Sign up to set email alerts
|

The provision of citizenship education in Arab contexts

Abstract: Since the early 1990s, citizenship education has occupied a high profile in educational policies worldwide. Yet, this area has not received similar attention in Arabic countries as has been shown by some studies that have until now focused on this area. This article is a first attempt to review the available literature in order to provide some indicators and insights regarding the current provision of citizenship education (CE) in Arab contexts. Specifically, the article starts by providing a brief geographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It has a combined population of around 422 million people, with over half under 25 years of age (Mazawi & Sultana, ). Yet, as Arab countries are not completely similar in terms of political, economic, cultural and social aspects, Almaamari () suggests using the term ‘Arab contexts’ to demonstrate the colourful, diverse nature of the term ‘Arab world’. In this sense, one may look at this term as deriving from a defining discourse that represents an institutionalised way of thinking about societies (Said, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has a combined population of around 422 million people, with over half under 25 years of age (Mazawi & Sultana, ). Yet, as Arab countries are not completely similar in terms of political, economic, cultural and social aspects, Almaamari () suggests using the term ‘Arab contexts’ to demonstrate the colourful, diverse nature of the term ‘Arab world’. In this sense, one may look at this term as deriving from a defining discourse that represents an institutionalised way of thinking about societies (Said, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, this field has not received the same attention in the Arab countries, as indicated by the studies that have thus far focused on this field [24]. Furthermore, indicators, ideas, and experiences regarding GCED in Arab contexts indicate that there are several difficulties in introducing citizenship education into the curricula and determining its content and manner of presentation [25]. Likewise, the idea of promoting global citizenship has gained momentum in education as part of a movement to advance twenty-first century skills or critical thinking skills in Oman [26].…”
Section: Oman Gced Experience and Its Challengesmentioning
confidence: 99%
“…Similarly, some studies conducted in Oman have shown that GCED is still associated with the field of social studies [9,25,27]. Therefore, the role of other subjects such as English, geography, science, and Islamic culture must be strengthened in order increase the effectiveness of GCED.…”
Section: Oman Gced Experience and Its Challengesmentioning
confidence: 99%
“…The lack of credible democratic citizenship education programmes in most if not all the countries in the Arab and Muslim world is confirmed by the fact that these countries hardly focus on the cultivation of democratic discourses. Instead, the concept of democratic citizenship education does not appear widely in Arabic educational literature and only the concepts of al‐tarbiyyah al‐wattaniyyah (national education) and al‐tarbiyyah al‐madaniyyah (civic education) are used (Al‐Maamari, , p. 38). In those countries in which citizenship education is given some consideration emphasis seems to be placed on ‘social cohesion’ or co‐existence (Lebanon); ‘combating rebellion against authority’ such as riots, suicide operations, and belonging to armed opposition (Algeria); ‘confronting growing threats and proliferation of extremist groups’ (Egypt); ‘appreciation for government’ (Oman); ‘loyalty to homeland’ (Sudan, Saudi Arabia and Jordan); ‘patriotism’ (Libya); and ‘allegiance to the King’ (Bahrain) (Al‐Maamari, , p. 42).…”
Section: On the Inadequateness Of Civic And National Education In Thementioning
confidence: 99%
“…It seems as if political literacy and critical thinking (aspects of democratic engagement) are given less attention in Arab and Muslim contexts. For instance, in Lebanon civic education places more emphasis on ‘obedience rather than participation’ (Akar, , p. 61); in Saudi Arabia's national education programmes ‘student teachers tend to avoid politics as it might trouble their lives’ (Al‐Maamari, , p. 43); and in Oman civic education is ‘not an integral component in teachers’ preparation programme (Al‐Maamari, , p. 44). Hence, the dearth of democratic citizenship education programmes in the afore‐mentioned countries has left their education systems vulnerable to the dominance of authoritarian values, lack of opportunities for participation in governance and decision‐making, prevalence of non‐democratic and corrupt political regimes and the curtailment of freedom of speech and belief.…”
Section: On the Inadequateness Of Civic And National Education In Thementioning
confidence: 99%